“THE IMPORTANCE OF PHONEMES IN LANGUAGE LEARNING” (Ustozlar uchun, 2026)
This article provides information about phonemes, which are the smallest units of sound that help distinguish meaning in words. It also discusses the importance of phonemes in the process of learning a language. The purpose of this article is to show how phoneme awareness improves pronunciation and communication during language learning.